Corporate tax audit in Malaysia: an exploratory study using focus groups - Isa, Khadijah; Pope, Jeff (Thomsons Reuters, 2010)
This article aims to explore the major issues encountered by corporate tax auditors when discharging their duties under a self-assessment system (SAS). Data drawn from focus group interviews conducted in early 2009 involving 60 tax auditors from the Inland Revenue Board Malaysia (IRBM) indicated three key issues of concern, namely, the welfare of tax auditors, tax complexity and tax education. These findings can benefit tax authorities by providing some insights for future policy plans pertaining to tax audits and tax education programmes. In regard to the generalisation made based on these findings, this study has taken several precautions to ensure that the composition of the focus groups was representative of all auditors. The use of focus groups to explore the experience of corporate tax auditors provides a significant and extensive contribution to the current knowledge and literature on corporate taxpayers’ compliance behaviour. The article concludes with some suggestions to overcome the central emerging issues.